What did Xenophanes Know? Fragment B 34 of Xenophanes’ Colophon as an Invective - Śpiewak, Sebastian (Folia Philosophica, 2024)
The purpose of this article is to analyze the main assumptions and exegetical strategies used by representatives of the so-called invective interpretations of Xenophanes’ philosophy. In addition to the models of imputing scepticism or empiricism to the poet’s position, they constitute a third group of possible ways of reading the passage B 34 of the Colophonian. The article points where to look for weaknesses in the arguments proposed by the representatives of the understanding of B 34 as invective, and in what sense these interpretations can contribute to a deeper understanding of Xenophanes’ novel conception of philosophy, especially in the context of the development of individualistic archaic poetry. The need for further research that takes into account the key question of the positive component of the poet’s philosophy in invective interpretations will also be indicated.